A new species of Pristimantis (Anura: Craugastoridae) from the western slopes of the Serranía del Baudó, Chocó, Colombia - Garzón-Franco, Esteban; Durango, Juan-P.; Ospina-Sarria, Jhon Jairo; Arredondo, Juan C. (Zootaxa, 2026)
We describe a new species of Pristimantis based on morphological and acoustic evidence from the western slopes of the Serranía del Baudó, tentatively assigned to the Pristimantis ridens species group. The new species can be distinguished from congeneric species by having coppery or reddish bronze iris, with fine black reticulations and light blue sclera, upper eyelid bearing one to three subconical tubercles, posterior surfaces of thighs generally solid brown, with small cream specks present in a few cases and groin solid brown, with some individuals showing a cream or golden blotch. Moreover, this new species distribution is notably distant from the other most similar species, inhabiting the humid lowland tropical forests of the western slopes of the Serranía del Baudó. With the description of this new species, the Pristimantis ridens species group reaches 31 species, that can be found in the Andean and Pacific regions from Central America to northern Peru.